Dracula Meets the Music Video - Tomasz Fisiak (Zagadnienia Rodzajów Literackich)
The following article will attempt to establish an intertextual link between one of the seminal examples of Gothic literature, i.e., Bram Stoker’s Dracula (1897), and the still relatively new medium of music video. To narrow down the analysis, I aim to explore intertextual connections between a particular cinematic rendition of Stoker’s novel, namely Friedrich Wilhelm Murnau’s 1922 Nosferatu: A Symphony of Horror (Nosferatu, eine Symphonie des Grauens), and three selected music videos. These are the Pet Shop Boys’ “Heart” (1988, directed by Jack Bond), Myslovitz’s “Dla ciebie” (2000, directed by Krzysztof Pawłowski) and Bad Bunny’s “Baticano” (2023, directed by Stillz). Even though all three of them openly reference the aforementioned masterpiece of German Expressionism, they were created in three different decades (the 1980s, 2000s, 2020s), in three different countries (UK, Poland, Puerto Rico) and represent three different music genres (pop, rock, trap/reggaeton), thus demonstrating the enduring influence of Murnau’s adaptation and, by extension, Stoker’s source text. To sum up, my intention is to track the affinities between the film (and, vicariously, the novel) and the videos, with a particular focus on visual intertexts, to examine how Gothic tropes and motifs are rewritten and adjusted to modern contexts to form new meanings and a series of fruitful encounters.